Three-Phase Two-Leg T-Type Converter based Active Power Filter - Biricik, Samet; Komurcugil, Hasan; Trabelsi, Mohamed (IEEE, 2019)
In this work, a three-phase two-leg T-type active power filter topology is investigated when a three-level hysteresis band current modulation technique is applied. The three-phase two-leg T-type configuration which utilizes eight switching devices together split dc link capacitor banks is able to improve the reliability of the system as well as effectively reduces the power losses. The compensation of the current harmonics at each phase are achieved successfully with the control of phase-a and phase-b. Using this technique, the phase-c is directly connected to the midpoint of the split capacitors, which eliminates the necessity of additional control on the phase-c. The performance of the proposed topology and control method is demonstrated through the simulation results.
45th Annual Conference of the IEEE Industrial Electronics Society (IECON) -- OCT 14-17, 2019 -- Lisbon, PORTUGAL
Keywords: Reduced number of switches; T-Type NPC inverter; APF; Hysteresis current control